Multiple symmetric calculi in the duplex system ureterocoele - Bajaj, A; Hada, R; Shrestha, PM; Bajaj, SK (Journal of Institute of Medicine Nepal, 2009)
The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 33-35